Before the Scandinavian 'porn wave': the business and regulations of magazines considered obscene in Sweden, 1910–1950. Issue 1 (2nd January 2017) - Arnberg, Klara
ABSTRACT: In this article, the Swedish market for magazines considered obscene (by authorities, distributors, retailers, etc.) is analyzed, with a focus on the first half of the twentieth century. Obscene content was combatted with several recurrent strategies by popular movements, the joint daily press, distributors and retailers, in addition to Freedom of the Press cases. However, once the consensus about the problem of pornography had been broken, during which time pornographers found ways to circumvent these strategies, a pornographic market was able to develop. The magazines that were considered obscene had different sub-genres: humorous and satirical (in the 1910s and 1920s), sex education (in the 1930s), nudism (1930s onwards) and pin-up (1940s onwards). All of the magazines in various ways distanced themselves from pornographic or sexual commercialism, but were nonetheless treated as part of it. Later, Sweden became one of the 'forerunners' in developing a market for pornography. This article traces the prehistory of this development and elaborates on the circumstances that prevented the market from developing earlier on. The argument is made that the restrictions were more connected to corporatist-related regulations concerning retail and distribution than to legal actions.